2000
DOI: 10.1128/mcb.20.23.8748-8757.2000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cyclin D3-cdk4 Complexes in Fibroblasts Expressing and Lacking p27kip1 and p21cip1

Abstract: Our studies examined the effects of p27 kip1 and p21 cip1 on the assembly and activity of cyclin D3-cdk4 complexes and determined the composition of the cyclin D3 pool in cells containing and lacking these cyclin-dependent kinase inhibitors. We found that catalytically active cyclin D3-cdk4 complexes were present in fibroblasts derived from p27 kip1 -p21 cip1-null mice and that immunodepletion of extracts of wild-type cells with antibody to p27 kip1 and/or p21 cip1 removed cyclin D3 protein but not cyclin D3-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 51 publications
7
56
2
Order By: Relevance
“…Therefore, it is likely that p21 Cip1 and p27 Kip1 are implicated in assembly factor(s) of cyclin D-CDK4/6 complexes. However, the idea that p21 Cip1 /p27 Kip1 are essential activators of cyclin D-kinases conflicts with recent observations made by Bagui et al (2000). Although Cheng et al (1999) were able to remove virtually all of the CDK4 kinase activity from the extracts of wild type MEFs by immunodepletion of p21/p27-complexes, Bagui et al (2000) failed to reproduce these results.…”
Section: Introductioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Therefore, it is likely that p21 Cip1 and p27 Kip1 are implicated in assembly factor(s) of cyclin D-CDK4/6 complexes. However, the idea that p21 Cip1 /p27 Kip1 are essential activators of cyclin D-kinases conflicts with recent observations made by Bagui et al (2000). Although Cheng et al (1999) were able to remove virtually all of the CDK4 kinase activity from the extracts of wild type MEFs by immunodepletion of p21/p27-complexes, Bagui et al (2000) failed to reproduce these results.…”
Section: Introductioncontrasting
confidence: 52%
“…However, the idea that p21 Cip1 /p27 Kip1 are essential activators of cyclin D-kinases conflicts with recent observations made by Bagui et al (2000). Although Cheng et al (1999) were able to remove virtually all of the CDK4 kinase activity from the extracts of wild type MEFs by immunodepletion of p21/p27-complexes, Bagui et al (2000) failed to reproduce these results. Moreover, Bagui et al (2000) showed the presence of cyclin D3-CDK4 kinase activity in p21/p27-null MEFs.…”
Section: Introductioncontrasting
confidence: 52%
See 1 more Smart Citation
“…To account for previously reported preferential binding of p21 to the Cdk2 complex upon UV irradiation of mammalian fibroblast cells , it is possible that majority of the pre-existing Cdk4 complex has already been associated with and inactivated by p27 (Polyak et al, 1994;Toyoshima and Hunter, 1994;Bagui et al, 2000;Bagui et al, 2003) and thus does not need p21 binding for inactivation. In this context, it is noteworthy that DAP treatment of A2780 cells induces a great increase in the amount of the Cdk4 and Cdk2 complexes (Figure 2), making the pre-existing p27-containing Cdk4 complex quantitatively less significant in the final population of the inhibited Cdk4 complex.…”
Section: Discussionmentioning
confidence: 99%
“…CDK activation requires cyclin association, and cyclin-CDK activity is negatively regulated by a group of proteins termed CDK inhibitors (CKIs). The CKI family includes p21 Cip1 and p27 Kip1 , both of which interact with and inhibit the activity of complexes containing the D cyclins and cdk4 or cdk6, cyclin E and cdk2, and cyclin A and cdk2 (Bagui et al, 2000;Sherr and Roberts, 1995). When active, these complexes implement G0/G1 progression and S phase entry.…”
Section: Introductionmentioning
confidence: 99%